2010
DOI: 10.1111/j.1523-536x.2009.00372.x
|View full text |Cite
|
Sign up to set email alerts
|

Inconsistent Evidence: Analysis of Six National Guidelines for Vaginal Birth After Cesarean Section

Abstract: VBAC guidelines are characterized by quasi-experimental evidence and consensus-based recommendations, which lead to wide variability in recommendations and undermine their usefulness in clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
23
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 24 publications
2
23
1
Order By: Relevance
“…For example, the Royal College of Obstetricians and Gynaecologists' Green-Top Guidelines [35] state that "planned VBAC should be attempted in a suitably staffed and equipped delivery suite, with continuous intrapartum care and monitoring and available resources for immediate cesarean section and advanced neonatal resuscitation" [p. 9]. Although this recommendation is based primarily on consensus and expert opinion rather than empirical evidence [38], it is clear that there is a level of international consensus that VBAC requires close vigilance during labor. Unfortunately, however, the recommended guidelines do not provide solutions to the real-world problem of staffing obstetrical units to meet the needs of women with a previous cesarean.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the Royal College of Obstetricians and Gynaecologists' Green-Top Guidelines [35] state that "planned VBAC should be attempted in a suitably staffed and equipped delivery suite, with continuous intrapartum care and monitoring and available resources for immediate cesarean section and advanced neonatal resuscitation" [p. 9]. Although this recommendation is based primarily on consensus and expert opinion rather than empirical evidence [38], it is clear that there is a level of international consensus that VBAC requires close vigilance during labor. Unfortunately, however, the recommended guidelines do not provide solutions to the real-world problem of staffing obstetrical units to meet the needs of women with a previous cesarean.…”
Section: Discussionmentioning
confidence: 99%
“…10,[35][36][37] Comparisons are challenging because of variations in study reports and limitations in data management and analysis. 38 This inconsistent information could understandably create confusion for pregnant women. 38 Nevertheless, women should be informed that both birth methods are not risk free.…”
Section: Literature Reviewmentioning
confidence: 99%
“…38 This inconsistent information could understandably create confusion for pregnant women. 38 Nevertheless, women should be informed that both birth methods are not risk free. 36,37 A successful VBAC rate of 60-82% has been shown with no significant difference in maternal death and hysterectomy between VBAC and repeat CS.…”
Section: Literature Reviewmentioning
confidence: 99%
“…'' 11(p29) Critical reviews of practice guidelines have shown them to vary considerably in the strength of evidence used in their development, the search methods employed to gather the evidence, and the demonstration of links between the evidence gleaned and the resulting practice recommendations. [12][13][14] With publication of the Appraisal of Guidelines for Research and Evaluation (AGREE) instrument in 2003 15 and recent expansion and improvement of the tool as the AGREE II, 16,17 it is now possible to address this variability in guideline quality by systematically evaluating key factors in guideline development. The AGREE II comprises 23 items within 6 domains: 1) scope and purpose; 2) stakeholder involvement; 3) rigor of development; 4) clarity of presentation; 5) applicability; and 6) editorial independence.…”
mentioning
confidence: 99%